PEDAGOGICAL DIGRESSIONS IN THE EDUCATIONAL PROCESS (INTERDISCIPLINARY APPROACH) - Горбачевська, Оксана; Халабова, Олена (Socio-economic relations in the digital society, 2019)
Modern globalization of society requires from its members a high level of knowledge, and in all areas. It is important for us to emphasize that economic education has undergone changes at the expense of other social sciences. There were priority not only questions of rational consumption, but also behavior model of the individual. A new branch in economics was formed — behavioral economics. It uses interdisciplinary connections of economics and psychology. As an example, the article considers two types of behavior — opportunistic behavior in the economy and the behavior of «professional deformation» in pedagogy. The first type is due to the asymmetry of available information in the market. The second type characterizes personality changes due to its professional activity. The second kind of behavior is correctable, since it is a reflection of the personality traits of the individual. It is possible to associate «Trojan learning» with the first look. According to the authors, two undesirable trends in economic education have emerged in connection with the intense competition in the labor market. Both are associated with non-sedulous relationof teachers to the professional craft. In article the conscious and unconscious non-sedulous learning of students called by «Trojan learning» is investigated. Irresponsible learning arises unintentionally, due to didactic errors and lack of knowledge of the teacher. The unconscious «Trojan learning» is intended to present the material in such way that the graduates do not become candidates for the position of teacher. The authors conducted a survey of students and teachers of the Lviv Institute of University of Banking on existence of «Trojan learning» in institute. Data analysis made it possible to uncover various forms of non-sedulous education, to give them an assessment. The authors see the path to overcoming these shortcomings in the development of professional competencies, as required by the Law of Ukraine «On Higher Education».
Keywords: behavioral economics; personality model; opportunistic behavior; professional deformation; Trojan learning; interdisciplinary communication; competencies